Image analysis of mechanistic protein biomarkers for the characterization of genotoxicants: Aneugens, clastogens, and reactive oxygen species inducers. (27th April 2020) - Wilde, Sabrina; Queisser, Nina; Sutter, Andreas
Abstract: The early detection of genotoxicity contributes to cutting‐edge drug discovery and development, requiring effective identification of genotoxic hazards posed by drugs while providing mode of action (MoA) information in a high throughput manner. In other words, there is a need to complement standard genotoxicity testing according to the test battery given in ICH S2(R1) with new in vitro tools, thereby contributing to a more in‐depth analysis of genotoxic effects. Here, we report on a proof‐of‐concept MoA approach based on post‐translational modifications of proteins (PTMs) indicative of clastogenic and aneugenic effects in TK6 cells using imaging technology (with automated analysis). Cells were exposed in a 96‐well plate format with a panel of reference (geno)toxic compounds and subsequently analyzed at 4 and 24 hr to detect dose‐dependent changes in PTMs, relevant for mechanistic analysis. All tested compounds that interfere with the spindle apparatus yielded a BubR1 (S640) (3/3) and phospho‐histone H3 (S28) (7/9) positive dose–response reflecting aneugenicity, whereas compounds inducing DNA double‐strand‐breaks were associated with positive FANCD2 (S1404) and 53BP1 (S1778) responses pointing to clastogenicity (2/3). The biomarker p53 (K373) was able to distinguish genotoxicants from non‐genotoxicants (2/4), while the induction of reactive oxygen species (ROS), potentially causing DNA damage, was associated with a positive Nrf2 (S40) response (2/2). This work demonstrates that genotoxicants and non‐genotoxicants induce different biomarker responses in TK6 cells which can be used for reliable classification into MoA groups (aneugens/clastogens/non‐genotoxicants/ROS inducers), supporting a more in‐depth safety assessment of drug candidates.